Awareness and Beliefs Towards Organ Donation in Chronic Kidney Disease Patients: A single center experience. (August 2017) - Balwani, Manish; Patel, Mohan; Goswami, Jitendra; Kute, Vivek; Trivedi, H.L.; Shah, Pankaj
Abstract : Introduction: There is a wide discrepancy between demand for and availability of donor organs for organ transplantation. There is no study on awareness about organ donation in chronic kidney disease (CKD) patients in India. Objectives: To study the awareness and beliefs towards organ donation in CKD patients on hemodialysis in western India. Patients and Methods: Authors conducted a cross sectional study among 85 CKD patients to evaluate knowledge about and attitude towards organ donation at a tertiary hospital. Results: Age of respondents ranged from 15 to 75 years. All were aware of term organ donation and cadaver donation. About 47% of people heard about organ donation through hospital or from doctor. Strikingly, radio was not the source of information to any of the respondents, despite radio being one of the most common medium of mass communication. Almost one third of patients were unaware about any legislation regarding organ donation. All respondents felt that organs should go to the needy irrespective of their religion. About 70% feel that medical colleges should make decisions about organ donation in case of unclaimed dead bodies. About 31.76% believe that there is a danger that donated organs could be misused, abused or misappropriated. Conclusion: Our study shows about 31.76% of our participants believe that there is a danger that donated organs could be misused, abused or misappropriated. There seems to be paucity of information and awareness regarding organ donation among CKD patients. Mass media, religious and political leaders may be involved to maximize awareness about organ donation.